The Knowledge Of Reproductive Health With Adolescent Behavior In Soe Christian Vocational School 2019: Hubungan Pengetahuan Kesehatan Reproduksi Dengan Perilaku Pacaran Pada Remaja Di Smk Kristen Soe Tahun 2019 - Ertiana, Dwi; Ottu, Alisa (Universitas Muhammadiyah Sidoarjo, 2020)
Technological advances have both positive and negative impacts on adolescents, especially in dating behavior. Dating behavior has the same meaning as the knowledge of the pros and cons. The problem faced by adolescents today is the large number of promiscuity, so they must have a positive attitude in dating behavior in order to avoid negative thoughts from the dating behavior. This study aims to determine the relationship between knowledge of reproductive health and dating behavior of adolescents at SMK Kristen Soe. The design of this research is correlational analytic with cross sectional approach. The population was 44 students in class XI Software Engineering who were taken by simple random sampling technique by paying attention to the inclusion criteria (students willing to become respondents and dating) and exclusion criteria (students not attending the research), so that a sample of 31 respondents was obtained. . Data collection was carried out on May 13-24 2019. Data collection used a questionnaire. The results showed that from 31 respondents got information about knowledge of reproductive health and dating behavior, namely 29 respondents (94%) and had good knowledge, namely 18 respondents (58.1%) and had healthy dating behavior, namely 23 respondents (74.2%) . The results of the analysis used the Spearman Rank test with p-value = 0.000 ˂ ɑ = 0.05 with a value of C = 0.771. Knowledge can also influence a person's behavior. Through his knowledge, a person will tend to agree on various things according to the object of behavior.